Mathematical model to reduce the lead time at workstations - Najib , Md Saad (2013)
In the modern’s era, the efficiency in workstations assembly line (AL) of manufacturing industry is very crucial and important in dealing with the customers and market demand. In addition, the automotive industry is one of the most important industries in the world nowadays. The automotive manufacturing industries have many shops and workstations. Each workstation has a number of operations including tasks that delegated. The operations and task is depend on the assemble product on body car. One of these shops is Assembly line shop. The scope of this study is focusing on the Assembly Line Shop (ALS) in the Automotive Assembly Line. The problems that occur in the assembly line shop concern queuing and idle time that will directly affect to the lead time between workstations. In this study, it discusses about to minimize the lead time at assembly line and to maximize the process time at workstations by using mathematical model. A mathematical model was applied to maximize the process time all operations in all workstations at the same time and to reduce the lead time in transferring the car structure and part between stations during assemble. The result showed that saving time and ensuring maximum production can increase profits in the automobile manufacturing industry. The time frame covered is one year it is in the year of 2013. This study is conducted by using the mathematical model and using MATLAB software to solve it.